PEMBELAJARAN KITAB AL-ARABIYAH LINNASYIIN DENGAN METODE LANGSUNG UNTUK MENINGKATKAN KEMAMPUAN BERBICARA DI SMP SALAFI DI INSTITUT ABU HURAIRA MATARAM - Muhammad Aminullah; Abdul Aziz; Fahrurrozi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine how to learn the Al-Arabiyah Linnasyiin book with a direct method to improve speaking skills in Salafi Junior High Schools at the Abu Huraira Institute, Mataram and to analyze the problems in learning the Al-Arabiyah Linnasyiin book with a direct method to improve speaking skills. This study used a qualitative field method with a focus on teaching Arabic to young people at Salafi Junior High Schools at the Abu Huraira Institute, Mataram through a direct, audiovisual, and visual approach. Data were collected through interviews, observations, and documentation from the principal, teachers, students, dormitory supervisors, and OSIS, and were analyzed in a structured manner to understand the effectiveness of learning. This study shows that learning Arabic at Salafi Junior High Schools at the Abu Huraira Institute uses the Arabic for Juniors book as a strategy to improve students' language skills. This book is designed for non-Arabs, focusing on four main skills (listening, speaking, reading, writing) with a direct method without translation. The full use of Arabic familiarizes students and prepares them for higher levels. The learning method prioritizes direct interaction and continuous practice in the classroom and dormitory. Teachers apply a participatory approach by involving students in direct conversation and practice. A consistent Arabic-speaking environment and adequate teacher competence make learning interactive and enjoyable. However, there are challenges, such as students' diverse educational backgrounds, difficulties in reading the Qur'an, limited learning facilities, and the influence of a mixed environment with other institutions. The solution needed is to provide a special place so that Arabic language learning is more optimal.